The therapeutic effect of chlorogenic acid against Staphylococcus aureus infection through sortase A inhibition - Wang, Lin; Bi, Chongwei; Cai, Hongjun; Liu, Bingrun; Zhong, Xiaobo; Deng, Xuming; Wang, Tiedong; Xiang, Hua; Niu, Xiaodi; Wang, Dacheng (Frontiers in Microbiology, 2015)
The emergence and wide spread of multi-drug resistant Staphylococcus aureus (S. aureus) requires the development of new therapeutic agents with alternative modes of action. Anti-virulence strategies are hoped to meet that need. Sortase A (SrtA) has attracted great interest as a potential drug target to treat infections caused by S. aureus, as many of the surface proteins displayed by SrtA function as virulence factors by mediating bacterial adhesion to specific organ tissues, invasion of host cells, and evasion of the host-immune responses. It has been suggested that inhibitors of SrtA might be promising candidates for the treatment and/or prevention of S. aureus infections. In this study, we report that chlorogenic acid (CHA), a natural compound that lacks significant anti-S. aureus activity, inhibit the activity of SrtA in vitro (IC50 = 33.86 ± 5.55 μg/ml) and the binding of S. aureus to fibrinogen (Fg). Using molecular dynamics simulations and mutagenesis assays, we further demonstrate that CHA binds to the binding sites of C184 and G192 in the SrtA. In vivo studies demonstrated that CHA prevent mice from S. aureus-induced renal abscess, resulting in a significant survival advantage. These findings indicate that CHA is a promising therapeutic compound against SrtA during S. aureus infections.